1974
DOI: 10.1254/jjp.24.447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acetylcholine Releasing Drugs on Electrical Activities Obtained From Auerbach's Plexus in the Guinea Pig Ileum

Abstract: Abstract-Effectsof 5-hydroxytryptamine, sodium picrate, caerulein and pentagastrin on the electrical activities obtained from Auerbach's plexus in the guinea pig ileum were investigated. The drugs used increased the spike frequency and increase of the spike frequency induced was inhibited by morphine but not by atropine and hexa methonium.The muscle spikes obtained simultaneously were inhibited by atropine. These facts indicate that the drugs used stimulate Auerbach's plexus and accelerate the acetylcholine re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Previous studies with extracellular recording from myenteric neurones, showed predominantly excitatory effects of 5-HT (Sato et al 1974;Dingledine et al 1974). Extracellular suction electrodes record activity almost exclusively from S-cells (Dingledine & Goldstein, 1976;North & Williams, 1977) and it is appropriate that the predominant response of S-cells to 5-HT in the present study was a membrane depolarization (Tables 1 & 2).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous studies with extracellular recording from myenteric neurones, showed predominantly excitatory effects of 5-HT (Sato et al 1974;Dingledine et al 1974). Extracellular suction electrodes record activity almost exclusively from S-cells (Dingledine & Goldstein, 1976;North & Williams, 1977) and it is appropriate that the predominant response of S-cells to 5-HT in the present study was a membrane depolarization (Tables 1 & 2).…”
Section: Discussionmentioning
confidence: 82%
“…In contrast, 5-HT inhibits the peristaltic reflex evoked in isolated pieces of ileum (Kosterlitz & Robinson, 1957;Biilbring & Crema, 1958) and also inhibits the contraction of the ileum brought about by stimulating the intramural nerves (Gintzler & Musacchio, 1974). When myenteric neurones are induced to fire by contact with a fine suction electrode, 5-HT has predominantly excitatory effects (Sato, Takayanagi & Takagi, 1974;Dingledine, Godstein & Kendig, 1974), but when the membrane potential of myenteric neurones is recorded directly with intracellular electrodes, the consistent effect of 5-HT is presynaptic inhibition of acetylcholine release (Henderson & North, 1975;North, Henderson, Katayama & Johnson, 1980). However, in a proportion of cells 5-HT has direct effects on the membrane of the myenteric neurones (Henderson & North, 1975;Wood & Mayer, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have shown that cells of both the myenteric and submucous plexuses of the small and large intestine can be excited by ACh and other nicotinic agonists (Wood, 1970;Ohkawa & Prosser, 1972;Sato, Takayanagi & Takagi, 1974;North & Nishi, 1976). These cells demonstrate a fast synaptic input that is mediated by nicotinic receptors (Nishi & North, 1973;Hirst, Holman & Spence, 1974;Suprenant, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Fine suction electrodes were used by Dingledine and co-workers (41)(42)(43), North and Williams (160,161), and Sato et al (186,187), while the others used either metal or glass pipette electrodes for single-unit recording. The group in Leningrad was the first to record from myenteric neurons with the intestine in situ and blood flow intact (73,110,164).…”
mentioning
confidence: 99%